Centralized Wireless Sensor Network Deployment - Mageswaran, R. Jaganathan (UTeM, 2010)
Wireless Sensor Network has become the new trend of sensing parameter such as temperature, humidity, pressure and etc. Even though the technology has been invented late of 90‟s but this technology is still new for Malaysia. The Sensor node will be responsible to transfer the data of sensed parameter to base station. There are many topologies that can be used to arrange the sensor nodes. These topologies are star (centralized), mesh, tree and etc. The topology depends on the usage and the environment of the sensor nodes placed. This project is about the deployment of the Wireless Sensor Network using the centralized topology to sense the temperature and humidity. Centralized topology is used due to simplicity and wider range of coverage. All nodes are connected to a single base station. The base station requires greater message handling, routing, and decision-making capabilities than the other nodes. The main issue about this Wireless Sensor Network is the energy consumption of the sensor nodes. Since the sensor node using battery as the power supply, so the energy consumption must be reduced so that the sensor node‟s life span will be higher. The optimization of the energy consumption of sensor node will be done by manipulating the RF Power and Sampling Rate of the each sensor node.